VD_FINDINFO Jug / 2017 / 88 vom 9. August 2016 - VD Tribunal cantonal (2016)
LÉSION CORPORELLE GRAVE, NÉGLIGENCE, PLAIGNANT, QUALITÉ POUR AGIR ET RECOURIR, TORT MORAL, PARTIE CIVILE | 47 CO, 125 al. 2 CP, 33 al. 2 CP, 118 CPP (CH), 126 CPP (CH)